Little birds : erotica - Nin, Anaïs, 1903-1977 (Harcourt, 2004)
Overview: Evocative and superbly erotic, Little Birds is a powerful journey into the mysterious world of sex and sensuality. From the beach towns of Normandy to the streets of New Orleans, these thirteen vignettes introduce us to a covetous French painter, a sleepless wanderer of the night, a guitar-playing gypsy, and a host of others who yearn for and dive into the turbulent depths of romantic experience. Few women writers dare celebrate the sexual experience as fully as Anais Nin. Taking off where Delta of Venus left off, Little Birds explores passion in all its forms. Evocative, compelling and superbly erotic, this is a powerful journey into the mysterious world of sex and sensuality.